ro-9: ropy-9 (R2526) is apparently an allele of da: dapple (R2375) in Neurospora. - D. D. Perkins (Fungal Genetics Reports, 1986)
ro-9: ropy-9 (R2526) is apparently an allele of da: dapple (R2375) in Neurospora.